An International Civil Law Approach to the Legal Certainty of Same-Sex Marriage with Differences in Citizenship (Case Study of Ragil Mahardika and Fred Vollert Frederik) - Nurhan, Cinta Annata; Erwanto, Nabila Mauldy; Gisna, Eva Shifdlotul; Salsabil R P, Frisca Zalfa; Sabila, Fanim Angelina (Journal of Legal and Cultural Analytics, 2023)
The phenomenon of same-sex marriage is a phenomenon that is widely discussed in society. The marriage of Ragil Mahardika and Fred Vollert Frederik contains foreign elements when viewed from the perspective of the subjects who are citizens of different countries, Indonesia & Germany. Their marriage can be considered valid in Germany in accordance with the principle of "Lex Loci Celebrationis" which means that the law that applies to a marriage is in accordance with the law of the place where the marriage took place but cannot be said to be valid. If we refer to Indonesian state regulations, the benefit of this writing is to know for sure whether the marriage can be said to be valid or not. The research method used in this research uses normative juridical by studying and analyzing social phenomena that occur in society in order to understand the conditions and solutions to the problems that occur. This article was written about same-sex marriage to find out whether the marriage can be said to be legal or not.